Systems Engineering roles to handle emergent properties and behaviors in complex technical systems - Gräßler, Iris; Pfeifer, Jan Niklas; Hintz, Florian; Meyrl, Nicolas (INCOSE International Symposium)
Abstract Engineering projects for complex technical systems such as automobiles demand extensive requirement specifications and corresponding hierarchy levels in system architectures. Especially when considering emergent phenomena, such as total weight or aerodynamics, a closely networked collaboration of discipline‐specific and cross‐disciplinary roles is required. Further, in large organizations with a group structure, resulting functional and non‐functional contents need to be managed by distinct Systems Engineering roles. For example, the role “property manager” takes care of achieving overarching product properties, such as weight or aerodynamics, which cannot be directly fixed, but result from many specifications. This paper proposes new Systems Engineering roles and their application in a German Original Equipment Manufacturer (OEM). For validation, the roles have already been applied in everyday engineering projects at the OEM. The concept proved to be indispensable and transferable to other Systems Engineering projects.
Keywords: Systems Engineering roles; properties; features; emergent phenomena; automotive

Evolving Roles in Systems Engineering —‐ Insights from Germany's Mechanical and Plant Engineering Sector - Kaiser, Lydia; Wilke, Daria; Förster, Felix; Köhler, Ingmarie; Dumitrescu, Roman (INCOSE International Symposium)
Abstract Systems Engineering is developing differently in each sector and region. In German industry, especially in mechanical and plant engineering, Systems Engineering is of major importance. The introduction of Systems Engineering raises the question of which roles and competencies are required. This article examines the evolution of roles in Systems Engineering from a German perspective. Based on a literature review, the evolution of the identified Systems Engineering roles over time is shown, starting with the seminal publication by Sheard in 1996. It points out that only minimal adjustments and occasional role renaming have occurred. However, the review shows a common understanding of essential areas of responsibility within the SE and changes over time. The next step is to examine the current understanding of Systems Engineering roles in the industry. A quantitative analysis of job postings in Germany reveals a diverse interpretation of the term 'Systems Engineer; more than half of the positions cannot be categorized according to the INCOSE definitions. The job postings are used to determine which tasks are associated with the job, how often they occur, and in what combination. The primary responsibilities of systems engineers include creating and managing requirements, architecture processes, validation, and verification processes, and coordinating with customers and stakeholders. Finally, three representative companies from the mechanical and plant engineering sector were selected to analyze existing roles and tasks. From this, a common understanding of tasks and responsibilities is combined and organized into clusters. These are used by the companies to locate and thus derive their roles. The result is in an integrative approach that enables companies, especially in the midsize and medium sectors, to design the introduction in line with stakeholder demands. In summary, the industry's ongoing adaptation necessitates the evolution of Systems Engineering roles and competencies for successful and sustainable development and implementation of systems.